Development and application of a high-sensitivity immunochromatographic test strip for detecting pseudorabies virus - Yin, Jiajia; Liu, Huimin; Chen, Yumei; Zhou, Jingming; Liu, Yankai; Liang, Zhenglun; Zhu, Xifang; Liu, Hongliang; Ding, Peiyang; Liu, Enping; Zhang, Ying; Wu, Sixuan; et al. (Frontiers in Microbiology, 2024)
Pseudorabies (PR) is a multianimal comorbid disease caused by the pseudorabies virus (PRV) for which pigs are the natural reservoir. At the end of 2011, the emergence of PRV variant strains in many provinces in China caused huge economic losses to pig farms in China. Rapid detection diagnosis of pigs infected with PRV variant helps prevent outbreaks of PR. Immunochromatography test strip with colloidal gold nanoparticles is often used in clinical testing due to its low cost and high throughput. This study was designed to produce monoclonal antibodies targeting PRV through the immunization of mice using the eukaryotic system to express the gE glycoprotein. Subsequently, paired monoclonal antibodies were screened based on their sensitivity and specificity for use in the preparation of test strips. The strip prepared in this study was highly specific, only PRV was detected, and there was no cross-reactivity with glycoprotein gB, glycoprotein gC, glycoprotein gD, glycoprotein gE of Herpes simplex virus and Varicella-zoster virus, Porcine epidemic diarrhea virus, Senecavirus A, Classical swine fever virus, Porcine reproductive and respiratory syndrome virus and Porcine Parvovirus. High sensitivity, detection limit of 1.336×10 3 copies/μL (the number of viral genome copies per microliter); The coincidence rate with the RT-PCR detection method was 96.4%. The strip developed by our laboratory provides an effective method for monitoring PRV infection and controlling of PR vaccine quality.